2005
DOI: 10.1017/s143192760550922x
|View full text |Cite
|
Sign up to set email alerts
|

The Aberration Corrected JEM-2200FS at Brookhaven

Abstract: The Brookhaven JEM-2200FS electron microscope has been installed recently. This JEOL instrument is a 200kV high-resolution field-mission TEM/STEM equipped with an in-column energy filter. When it is completed by the end of 2005, the instrument will have two CEOS Cs aberration correctors [1], one for the probe forming lens and the other for the objective lens [2], and a JEOL monochromator. Figure 1 shows the instrument at Brookhaven. To ensure the instrument will meet its specifications achieving sub-Å spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It was reported that with the objective lens corrector, the image resolution of the instrument in TEM mode can be improved from 0.19nm to 0.12nm [2]. The EELS performance (measured energy resolution without the monochromator was 0.7eV) using the Omega filter will be also presented [4].…”
mentioning
confidence: 99%
“…It was reported that with the objective lens corrector, the image resolution of the instrument in TEM mode can be improved from 0.19nm to 0.12nm [2]. The EELS performance (measured energy resolution without the monochromator was 0.7eV) using the Omega filter will be also presented [4].…”
mentioning
confidence: 99%